2014
DOI: 10.1371/journal.pone.0104743
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of HMGB1-Induced Angiogenesis by Cilostazol via SIRT1 Activation in Synovial Fibroblasts from Rheumatoid Arthritis

Abstract: High mobility group box chromosomal protein 1 (HMGB-1) released from injured cells plays an important role in the development of arthritis. This study investigated the anti-angiogenic effects of cilostazol in collagen-induced arthritis (CIA) of mice, and the underlying mechanisms involved. The expressions of HIF-1α, VEGF, NF-κB p65 and SIRT1 in synovial fibroblasts obtained from rheumatoid arthritis (RA) patients were assessed by Western blotting, and in vitro and in vivo angiogenesis were analyzed. Tube forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 32 publications
1
39
0
1
Order By: Relevance
“…HMGB1 is a ubiquitous non‐histone DNA‐binding protein, extracellularly it serves as a signalling molecule involved in acute and chronic inflammation, including pneumonia and arthritis . GL is the specific inhibitor of HMGB1.…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 is a ubiquitous non‐histone DNA‐binding protein, extracellularly it serves as a signalling molecule involved in acute and chronic inflammation, including pneumonia and arthritis . GL is the specific inhibitor of HMGB1.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, synovial inflammation and bone erosion were significantly inhibited by cilostazol treatment in a murine CIA model. Recently, it was found that cilostazol like resveratrol (a known SIRT1 activator) elevated HMGB1-induced decreased SIRT1 protein expression and activity, whereas HMGB1-stimulated NF-κB activation was strongly inhibited by cilostazol [18]. Shakibaei et al [19] reported that RANKL up-regulated p300 (a histone acetyltransferase) expression, which, in turn, promoted NF-κB acetylation.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Down regulation of SIRT1 or inhibition of sirtuin activities in synovial cells of RA patients was found to reduce the expression of inflammatory mediators [13,14], and overexpression of SIRT1 increased production of pro-inflammatory cytokines in rheumatoid arthritis synovial fibroblasts (RASF) and monocytes from healthy persons [13]. In contrast, levels of SIRT1 were diminished in joint tissues of mice with collagen-induced arthritis [15]. Moreover, deletion of SIRT1 aggravated inflammatory arthritis in serum transfer arthritis model and increased production of pro-inflammatory cytokines in macrophages [16].…”
Section: Introductionmentioning
confidence: 99%